Sustainability of Rituximab Therapy in Different Treatment Strategies: Results of a 3-Year Followup of a German Biologics Register - Richter, Adrian (Arthritis Care Res (Hoboken), 2014)
OBJECTIVE: To compare the approved treatment of rheumatoid arthritis using rituximab + methotrexate (RTX + MTX) versus the off-label treatment variants of RTX in monotherapy or RTX in combination with leflunomide (RTX + LEF). METHODS: We included RTX-naive patients enrolled in the German biologics register RABBIT (Rheumatoid Arthritis: Observation of Biologic Therapy) between 2007 and 2012 (n = 907) who started treatment with RTX. Three treatment regimens (RTX + MTX, RTX + LEF, and RTX monotherapy) were analyzed regarding therapy discontinuation, dropout, RTX retreatment, and concomitant glucocorticoid therapy. Effectiveness was evaluated with linear mixed models. RESULTS: Baseline patient characteristics were similar across treatment regimens, except for poorer functional status and more comorbidities in RTX monotherapy. Average doses of glucocorticoids were lower in RTX + LEF compared to the 2 other groups. The frequency and timing of RTX retreatment (P > 0.62) as well as improvement in the Disease Activity Score in 28 joints (DAS28) over time (P > 0.15) were similar in all treatment regimens. Within the first 12 months of treatment, the DAS28 decreased by 1.5 units, and between months 12 and 36, by a further 0.4 unit equally in all groups. Nevertheless, therapy discontinuation and dropout were significantly increased on RTX monotherapy (hazard ratio [HR] 1.7 [95% confidence interval (95% CI) 1.2–2.3]), and additionally when patients were rheumatoid factor negative (HR 1.5 [95% CI 1.0–2.1]). CONCLUSION: In patients who continue therapy, RTX + LEF, RTX monotherapy, and RTX + MTX seem to be equally effective. However, given the lower adherence rates on monotherapy, this treatment option is not sufficient for all patients. Since many patients are intolerant to MTX, more licensed RTX treatment options are needed.